2016
DOI: 10.18632/oncotarget.10021
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of TELO2 decreases survival in human high-grade gliomas

Abstract: High-grade gliomas are characterized with poor prognosis. To improve the clinical outcome, biomarker is urgently needed for distinguishing oncotarget in high-grade gliomas. Telomere maintenance 2 (TELO2) regulates S-phase checkpoint in cell cycle, and is involved in DNA repair. However, the role of TELO2 in survival outcome of high-grade gliomas is still not yet clarified. This study aims to investigate the correlation between TELO2 mRNA expression and survival outcome of patients with high-grade gliomas. Base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…The differential expression of TELO2 during the various stages of CRC offset its role in the prognosis suggesting that TELO2 plays a distinctive role in the development of CRC. The role of TELO2 in the prognosis of CRC, which differs from that in breast cancer (14), is still unclear, indicating that mechanism of TELO2 is different in various cancers. Next, we needed to confirm the mechanism of TELO2-induced cancer progression in CRC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The differential expression of TELO2 during the various stages of CRC offset its role in the prognosis suggesting that TELO2 plays a distinctive role in the development of CRC. The role of TELO2 in the prognosis of CRC, which differs from that in breast cancer (14), is still unclear, indicating that mechanism of TELO2 is different in various cancers. Next, we needed to confirm the mechanism of TELO2-induced cancer progression in CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Degradation of TELO2 promotes the survival of multiple myeloma under growth factor withdrawal ( 12 ). Although there are several reports indicating that TELO2 demonstrates an oncogenic profile in solid tumors, such as breast cancer ( 13 ) and high-grade gliomas ( 14 ), the role and molecular mechanism of TELO2 in CRC tumorigenesis have yet to be defined. A study on TELO2 in CRC demonstrates that a germline mutation of TELO2 regulated the senescence pathway and is related to sessile serrated adenomas and adenocarcinoma progression ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study demonstrated that human high-grade gliomas show increased TELO2 mRNA expression and that the overexpression of TELO2 mRNA correlates with shorter survival outcomes, suggesting that TELO2 is an oncogene in human gliomas [16]. Here, we tried to figure out the oncogenic role of TELO2 in tumorigenesis.…”
Section: Resultsmentioning
confidence: 99%
“…TELO2 is not only critical for protein stability, but it is also essential for the integrity of mTOR complexes. Many studies have shown that TELO2 might play an oncogene role in solid tumors [11,[16][17][18]. Our previous study showed that Figure 8.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation